Embracing innovation to meet food systems challenges - Arndt, Channing; Chambers, Judith A.; Zambrano, Patricia; Alahmdi, Mohammed Issa; Alatawi, Aishah; Benfica, Rui; Edward, Martin G.; Gatehouse, Angharad M. R.; Moronta-Barrios, Felix; Ahmed, Akhter (T20, 2020)
Agrifood systems are powerful levers for improving livelihoods. They must also address an array of systemic challenges, including satisfying growing global food demand, improving diets, limiting greenhouse gas emissions, adapting to a warming climate, and sustaining the environment. Technology and innovation play a central role in meeting these challenges. This brief offers two policy recommendations to support the contribution of innovation. First, G20 countries should increase political and financial support to agrifood systems research in developing countries. Second, the G20 should promote and support science-based, responsible, and risk-assessed regulatory reforms that enable the safe deployment of promising bio-innovations.